A state-of-the-art review of energy-efficient and renewable energy systems in higher education facilities - Almasri, Radwan A.; Abu-Hamdeh, Nidal H.; Al-Tamimi, Nedhal (Frontiers in Energy Research, 2024)
Amid escalating energy demands and growing environmental concerns, educational institutions are transforming into crucibles for enduring innovation. This comprehensive review summarizes the complex relationship between Energy Efficiency and Renewable Energy Systems (EERES) within the sphere of educational institutions. By instituting Energy Efficiency initiatives, organizations can curtail energy consumption, resulting in substantial cost savings and a diminished carbon footprint. Moreover, the integration of renewable energy technologies empowers the localized generation of electricity, ensuring a reliable and sustainable energy source. Noteworthy in this study is the novel linkage of energy usage indicators to the comfort levels experienced in university settings during both summer and winter. An exhaustive examination of consumption indicators, rooted in the diverse activities on college campuses, further enriches the investigation. Beyond technical intricacies, this study scrutinizes the economic viability, environmental advantages, and educational significance of these integrated systems. Embracing EERES not only aligns with the commitment of educational institutions to environmental stewardship but also establishes a paradigm for broader communities. These institutions aspire to exemplify sustainable practices, influencing larger societal behavior positively. Various factors, including the institution’s type, energy source, facility nature, building construction, internal activities, weather conditions, and user behavior, wield substantial influence over energy utilization. This study offers a nuanced exploration, shedding light not only on the technical dimensions but also on the broader economic, environmental, and educational implications of adopting EERES.